Seismic hazard assessment of NW Himalayan fold-and-thrust belt, Pakistan using deterministic approach - Lisa, Mona; Khwaja, Azam A; Jan, MQ (Journal of Nepal Geological Society, 2008)
Seismic Hazard Assessment (SHA) of the entire seismically active NW Himalayan Fold and Thrust Belt that incorporates deterministic approach has been carried out for the first time. Additional information in the form of earthquake catalogue, delineation of 40 active faults in a structural map, their relationship to the seismicity, focal mechanism studies of 45 events, establishment of seismotectonic zones has also been undertaken. Distribution of 813 events within study area indicates that seismicity (?4.0 Mw) appears to be associated with both the surface and blind faults. At the same time, clustering of events in specific parts along the surface faults shows that some fault segments, especially in the hinterland zone are more active. In parts of the active deformational front like Salt Range, southern Potwar and Bannu, lesser seismic activity (?4.0 Mw) could be due to the damping effect of the thick Precambrian salt. Majority of the earthquakes (86%) range in magnitude from 4.0 to 4.9 Mw followed by 107 events (13%) having magnitude ranging from 5.0 to 5.9 Mw. The remaining 1% range from 6.0 to 6.7 Mw. There is a predominance of shallow seismicity (w) events from the adjoining areas, a deeper level of seismicity (50 to 200 km) prevails especially in the Hindukush Range of Afghanistan. Focal Mechanism Solutions (FMS) of 45 earthquakes (Mw?;4), including 21 from the Hinterland zone and 24 from the Foreland zone show dominance of strike slip faulting (27 out of 45). 11 indicate thrusting, 6 reverse faulting and 1 normal faulting solution. Tectonic complexity seems to be due to interplay of a variety of factors. Thrust and reverse solutions near the northern collisional boundary have mostly NE-SW directed P-axis orientations. Imbricate thrusting, breaking and thickening of the crust is believed to be occurring due to the steep bending of the underthrusting plate at the collisional boundary. Another compressional EW direction in the southwestern portion suggests the presence of a restraining bend in the Chaman Fault (the western plate boundary). A single normal faulting solution from this part could be similar to the one in the Central Salt Range and acting as a buttress to the south verging compression. Strike slip solutions from the hinterland zone are related to the ongoing uplifting in the Nanga Parbat-Haramosh massif and the Besham dome. In the foreland zone a regional shear couple between the N-S trending sinistral Chaman Fault and the Jhelum Fault at the western and eastern margins respectively is forming the Reidel structures (synthetic shears). A few strike slip solutions represent the P shears (secondary shears). Involvement of basement in the deformation process shows that models of thin-skinned tectonics formulated by different workers may not be valid. Considering a number of geological and seismological factors, four seismotectonic zones have been established. The b value for the Peshawar-Hazara Seismic Zone (PHSZ) is 1.16 followed by 1.12 for the Surghar-Kurram Seismic Zone (SKSZ). The other two, Swat-Astor Seismic Zone (SASZ) and Kohat-Potwar-Salt Range (KPSZ) have identical values of 0.95 thereby indicating occurrence of more events of relatively higher magnitude as compared to the other two seismic zones. Mean activity rate of earthquakes (l) ranges from 4.26 to 1.73. In decreasing order the values are 4.26, 2.62, 2.07 and 1.73 for PHSZ, SASZ, KPSZ and SKSZ respectively. Using 4 regression relationships, the maximum potential magnitude (m1) has been determined for the 40 Quaternary faults. In each seismic zone the highest value within the seismic zone represents its m1. Results show that m1 is 7.8 in the hinterland (SASZ and PHSZ) and 7.4 in the foreland part (KPSZ and SKSZ). SHA incorporating deterministic approach has been undertaken at 10 sites (Astore, Bannu, Kaghan, Kohat, Mangla, Malakand, Muzaffarabad, Peshawar, Talagang and Islamabad). Pakistan does not have an attenuation equation of its own. The two equations of Ambraseys et al., (1996) and Boore et al., (1997) have been used and the results obtained using the equation of Boore et al (1997) have been preferred. PGA’s estimated applying Deterministic Seismic Hazard Assessment (DSHA) shows higher values for Muzaffarabad (0.79g), Islamabad (0.75g), Kohat (0.75g) and Peshawar (0.64g). Lower values are obtained for Malakand (0.5g), Astore (0.47g), Talagang (0.47g), Kaghan (0.46g), Mangla (0.4g) and Bannu (0.27g). Important faults that can be potentially hazardous to all the sites have been identified. Journal of Nepal Geological Society, 2007, Vol. 36 (Sp. Issue) p.21